Inertia effects in a multilobe conical bearing lubricated with a couple stress fluid - Walicka, Anna; Walicki, Edward; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a multilobe conical bearing is analyzed. A lubricant modelled by a couple stress fluid flows in the bearing clearance . The Galerkin method is used to determine the mechanical parameters of multilobe journal bearings. An example of a two-lobe conical bearing is discussed in detail. The inertia of the flowing lubricant is taken into account in the analysis. It has been found that the increase of the couple stress generates an increase the pressure in the clearance.
Keywords: inertia effects; modified Reynolds equation; Galerkin method; mechanical parameters of bearing; additives